The relationships between cephalometric parameters and severity of obstructive sleep apnea - Sonsuwan N. (2014)
Objective: To verify the relationships between cephalometric parameters and apnea hypopnea index (AHI) in snoring patients in Chiang Mai University Hospital. Methods: Fifty patients who attend ENT snoring clinic, Faculty of Medicine, Chiang Mai University Hospital during 1 October, 2007 to 31 October, 2008 were enrolled. All subsequently underwent overnight polysomnography by SOMNOCHECK® V2.04 and lateral cephalometric radiographs. Results: Of the 50 patients, 78% were men (n=39) and 22% were women (n=11). Ages ranged from 31 to 65 years. Average apnea hypopnea index (AHI)=18.4±18.2events/h. Body mass index (BMI)=27.2±3.3kg/m2. The mean sella-nasion-subspinale (SNA)=84.1±4.3° Sella-nasion-supramental (SNB)=81.8±3.4° Posterior airway space (PAS)=14.9±4.3mm. Distance between mandibular plane and hyoid (MP-H)=27.7±5.6mm. Distance between posterior nasal spine and tip of soft palate (PNS-P)=42.5±5.4mm. Using Pearson's correlation analysis of BMI, the cephalometric parameters from all subjects with AHI revealed BMI, PAS and MP-H had significant correlation with AHI; p=0.009, p=0.003, and p=0.005, respectively. BMI, MP-H, and PAS were correlated with AHI. The multiple regression model for the effects of BMI, PAS, and MP-H on AHI is AHI=2.090(BMI)-1.953(PAS)+1.1333(MP-H)-40.54. Conclusion: The model seems to be useful as a screening tool to assess the severity of obstructive sleep apnea in snoring patients. © 2010 Elsevier Ireland Ltd.